Selenium status and cardiovascular risk factors in populations from different portuguese regions - Viegas-Crespo, Ana Maria (2014)
Proceedings de 2 Conferências simultâneas: "International Conference on Natural Antioxidants and Lipid Peroxidation in Atherosclerosis and Cancer (ALPAC)" e "International Conference on Quality and Safety Aspects and Nutrition in Europe'95 (QSFNE), 22-25 Agosto 1995, Helsínquia, Finlândia.